DETERMINAN TARIF PAJAK EFEKTIF PADA WAJIB PAJAK BADAN - Putri, Anggrieta Arzeni Gatra; Yanto, Heri (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2024)
This research aims to examine the influence of leverage, liquidity, profitability, independent commissioners, audit committees, and audit quality on the effective tax rate. The research approach used is a quantitative approach. The research population includes manufacturing companies from all sectors listed on the Indonesia Stock Exchange (IDX) during the period 2018-2022. Sampling was done using purposive sampling method, resulting in a sample size of 50 companies with 155 analysis units after excluding 95 outliers. Research data are secondary data taken from the IDX website and the websites of respective companies. The analysis technique used is multiple linear regression analysis technique using IBM SPSS 22 analysis software. The results of the research show that leverage and audit quality have a significant positive effect on the effective tax rate. Meanwhile, liquidity, profitability, independent commissioners, and audit committees do not affect the effective tax rate. Simultaneously, leverage, liquidity, profitability, independent commissioners, audit committees, and audit quality collectively influence the effective tax rate.